Hybrid synchronisation of vallis chaotic systems using nonlinear active control - Pratap Singh, Piyush; Kumar, Vikash; Tiwari, Eshan; K. Chauhan, Vinay (International Journal of Engineering and Technology, 2018)
In this paper, hybrid synchronisation of Vallis chaotic systems using a nonlinear control technique is proposed. Vallis system represents the principal quantitative features of the El-Nino Southern Oscillation (ENSO) phenomenon. A nonlinear active control technique is used for hybrid synchronisation. Control laws are designed by using the sum of the relevant variables of the both mater and slave systems. Required Lyapunov stability condition is devised using Lyapunov stability theory. Numerical simulation results reflect the successful achievement of the proposed objectives. MATLAB is used for simulation.Â Â